Identify the nonlinear wave‐particle interaction regime in rising tone chorus generation. Issue 8 (22nd April 2017) - Tao, Xin; Zonca, Fulvio; Chen, Liu
Abstract: Nonlinear wave‐particle interaction during chorus wave generation was assumed to be in the adiabatic regime in previous studies, i.e., the particle phase‐space trapping timescale ( τ tr ) is considered to be much smaller than the nonlinear dynamics timescale τ NL . In this work, we use particle‐in‐cell simulations to demonstrate that τ tr ∼ τ NL, i.e., the interaction regime during chorus generation is in the nonadiabatic regime. The timescale for nonlinear evolution of resonant particle phase‐space structures is determined by making the time‐averaged power exchange plot, which clearly demonstrates that particles with pitch angle near 80° make the most significant contribution to wave growth. The phase‐space trapping timescale is also comparable to the amplitude modulation timescale of chorus, suggesting that chorus subpackets are formed because of the self‐consistent evolution of resonant particle phase‐space structures and spatiotemporal features of the fluctuation spectrum. Key Points: Nonlinear wave‐particle interaction is demonstrated to be nonadiabatic The nonlinear evolution timescale is comparable to the particle phase‐space trapping timescale Subpacket formation is explained using phase‐space bounce motion of particles